Análise dos resíduos sólidos gerados em uma oficina mecânica - Peres, Vinícius de Ramos (2023)
Solid waste management is a growing global challenge as urbanization and consumption increase. Given this scenario, it is important to promote in-depth research into solid waste management in various areas and activities. In this sense, the objective of the work is to analyze the types of waste generated in a mechanical workshop, measuring the consequences that incorrect disposal can cause, both for the company and for the environment. The research involved data collection, using quantitative and qualitative analysis methods, being classified as exploratory in nature. In addition, existing segregation, packaging and disposal practices were evaluated, as well as possible risks to human and environmental health. In the end, through the matrix of environmental aspects and impacts and the 5w2h action plan, this study was successful in providing the necessary structure for the implementation of more effective waste management policies in the workshop in question, aiming to contribute to environmental sustainability in the automotive sector.